2007
DOI: 10.1002/lapl.200710123
|View full text |Cite
|
Sign up to set email alerts
|

Surgical performance of a 405-nm diode laser in treatment of soft tissue

Abstract: Abstract:The study was conducted to evaluate the surgical performance of a 405-nm diode laser ex vivo. The experiments were carried out using tuna tissue, which was irradiated with a 405-nm diode laser at output powers of 400 mW (694 W/cm 2 ) to 1 W (1735 W/cm 2 ) on a motorized stage moving at a rate of 1 mm/sec. As a control, a 920-nm diode laser was used with the same irradiation conditions. After irradiation, the thickness of ablation and coagulation was measured by stereoscopic microscopy and evaluated st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…In summary, our results suggest bFGF, a survivalpromoting agent, can effectively protect the retinal morphologic properties against the damaging effects of laser photocoagulation and preserve the visual function simultaneously, thereby enhancing the benefit obtained from laser application in clinic [29,30] and ensuring safe treatment for patients. Further studies of bFGF are expected to elucidate its possible cellular or molecular mechanisms, and to evaluate its potential role as an acceptable clinical therapy for this kind of laser-induced retinopathy, both accidental and iatrogenic.…”
Section: Discussionmentioning
confidence: 86%
“…In summary, our results suggest bFGF, a survivalpromoting agent, can effectively protect the retinal morphologic properties against the damaging effects of laser photocoagulation and preserve the visual function simultaneously, thereby enhancing the benefit obtained from laser application in clinic [29,30] and ensuring safe treatment for patients. Further studies of bFGF are expected to elucidate its possible cellular or molecular mechanisms, and to evaluate its potential role as an acceptable clinical therapy for this kind of laser-induced retinopathy, both accidental and iatrogenic.…”
Section: Discussionmentioning
confidence: 86%
“…30,35 The use of 405 nm diode laser with its narrow spectra has an advantage over common halogen light or light-emitting diode (LED) curing units with the peak at *470 nm; 10 the laser wavelength is within the specific visible range required for the photocatalyst, and unnecessary higher wavelengths emitted from incandescent lamps or blue LEDs that may be absorbed by the live tissue are avoided. 27 In this study, the parameter of the laser irradiation was determined within the specification of the laser and referring to previous studies.…”
Section: # #mentioning
confidence: 99%
“…29 An experimental violet diode laser with a wavelength of 405 nm was developed for oral surgery. 30 The wavelength of this laser is in the lowest part of the visible spectrum and appeared to be suitable for activating VL-TiO 2 of the bleaching agent. 9 In addition to the wavelength, other laser parameters may affect the outcome of irradiation; however, the effects of laser parameters on the performance of VLTiO 2 -containing bleaching agent are not known.…”
Section: Introductionmentioning
confidence: 97%
“…In 1996, Nakamura et al also invented the gallium nitride (GaN) violet-laser diode (VLD) [19], which was soon utilized widespread as light source for high-speed and multilayer recording systems such as Blu-ray Disc and HD-DVD systems [20]. This VLD technology also appears promising for medical applications, such as to cut soft tissue [21], for laser acupuncture [22], tooth whitening [23], and the detection of dental caries [26]. One has also suggested that the wavelength of violet-laser diode is suitable to cure dental adhesives/composites that include an CQ-amine alternative photo-initiator system.…”
Section: Introductionmentioning
confidence: 99%